A method for predicting the structure of corium pool in lower plenum of reactor vessel. (April 2019) - Liu, L.L.; Yu, H.X.; Chen, L.; Deng, J.; Deng, C.R.; Zhang, M.; Hou, L.Q.
Abstract: The corium in the lower plenum of reactor vessel is expected to stratify into two or three layers. The three-layer corium method adopted by MAAP5 code is based on Salay theory to treat the compositions in oxide and heavy metal layers and assumed that the light metal layer is formed automatically after the corium falls down. In this work, a method is designed for predicting the corium pool structure based on the accident progressions, especially, the formation of the light metal layer is not hypothetical and the condition of forming a three-layer corium pool is given. In addition, the heat flux distribution on the outside wall of the reactor vessel is analyzed with different corium pool structures. It is found that, the structure of the corium pool calculated by this method is unique while it is various calculated by MAAP5 code method, in which the composition of the light metal layer is user input. Although the thickest and thinnest light metal layer can be calculated by MAAP5 code method, the conservative heat flux still cannot be obtained, which confused the validity of IVR strategy. Highlights: A method is designed to predict the structure of corium in lower plenum. The compositions in each layer are influenced by accident progressions. The condition for a three-layer pool occurs is described. The heat flux on the outside of RPV is analyzed for corium pool structures.